Right menu

Featured resource

Count like an Egyptian: A hands-on introduction to ancient mathematics

Count like an egyptian

The mathematics of ancient Egypt was fundamentally different from the mathematics of today, which makes solving ancient Egyptian problems quite an adventure.

Members: $ 54.00 inc.GST Others: $ 67.50 inc.GST


‘Proof’ that 2 = 1

let a = b

then a2 = ab

a2 - b2 = ab-b2

(a-b)(a+b) = b(a-b)

a+b = b

substituting b+b = b

2b = b

2 = 1

Where is the error made?

You need to be aware that a – b = 0. This false proof relies on dividing both sides of an equation by zero which should not be done.